THE STRUCTURE OF THERMOLUMINESCENCE TRAPS IN AQUEOUS GROWN KCl - Ruchi Pandey; Kumar, Rajendra; Sumit Tiwari; S. D. Pandey (Malaysian Journal of Science, 2023)
The results of TL studies in aqueous grown undoped KCl crystals are reported. A de-convolution of TL curve into five component peaks has been performed and trap depths have been obtained. The importance of bi-vacancy has been established as a fundamental trap and its anion vacancy end has also been proposed as a suitable trap for thermoluminescence in KCl crystals. The traps at anion vacancies linked to impurity vacancy I-V pairs have also been envisaged and the shift in the depths of traps is attributed to the electric field of I-V pairs in the lattice caused by inherent divalent ions. Some traps linked to hydroxyl groups have also been identified.